Physical Properties of Denture Base Resins Potentially Resistant to Candida Adhesion - Gunjan Dhir, BDS, MS;1 David W. Berzins, PhD;2 Virendra B. Dhuru, BDS, (Journal of Prosthodontics, 2007)
The addition of anionic charge on denture base resins has been shown to inhibit Candida albicans adhesion and to facilitate adsorption of salivary defense molecules.